Computational analysis of Salmalia malabarica (Bombax ceiba) for the management of ulcerative colitis - Savita Bhosale, Prashant G. Jadar, Sunil S. Jalalpure, Vishal S. Patil, Kashinath Hiremath (Journal of Applied Pharmaceutical Science, 2024)
Bombax ceiba leaf petiole is used as an enema in the management of ulcerative colitis, but its molecular mechanisms are yet to be established. The current study employed gene set enrichment, network pharmacology, and molecular docking studies to infer the phytocompounds from B. ceiba responsible for the modulation of therapeutic targets of UC First, data of phytocompounds present in the leaf petiole were retrieved from the literature and public phytocompounds databases and their druggability and toxicity prediction was performed by MolSoft and AdverPred online servers, respectively. Furthermore, phytocompounds probable proteins were predicted by SwissTargetPrediction, and targets of UC were retrieved from the GeneCards database. A set of genes molecular pathways were identified by the STRING, Kyoto Encyclopedia of Genes and Genomics database, and pathways involved in UC were sorted and their network between compounds, targets, and pathways was constructed by the Cytoscape software. Molecular docking of hub-gene and targets was performed by the POAP pipeline. Out of 10 compounds, 7 (showed druggability in which Rutin scored the highest druglikeness score of 0.91. A total of 2830 genes were identified for UC, of which 39 matched with targets of phytocompounds (total of 297). These 39 targets were involved in 125 pathways, of which 14 were associated with UC mainly VEGF, IL-17, Neurotrophin, JAK-STAT, cAMP, TNF, TGF-beta, and NF-kappa B, MAPK, PI3K-Akt signaling pathway. Among the predicted targets, MAPK3, TNF, and PTGS2 were identified as a hub gene. Rutin scored the lowest binding energy of −7.9 kcal/mol and possessed 22 interactions with PTGS2 and Astragalin and Isoquercitrin were the next lead hit against PTGS2. It has been concluded that the use of B. ceiba leaf petiole could be a valuable source against UC.
Keywords: Bombax ceiba, molecular docking, network pharmacology, ulcerative colitis